Overexpression of DR-nm23, a protein encoded by a member of the nm23 gene family, inhibits granulocyte differentiation and induces apoptosis in 32Dc13 myeloid cells. - Venturelli, D (1995)
Chronic myelogenous leukemia evolves in two clinically distinct stages: a chronic and a blast crisis phase. The molecular changes associated with chronic phase to blast crisis transition are largely unknown. We have identified a cDNA clone, DR-nm23, differentially expressed in a blast-crisis cDNA library, which has approximately 70% sequence similarity to the putative metastatic suppressor genes, nm23-H1 and nm23-H2. The deduced amino acid sequence similarity to the proteins encoded by these two latter genes is approximately 65% and includes domains and amino acid residues (the leucine zipper-like and the RGD domain, a serine and a histidine residue in the NH2- and in the COOH-terminal portion of the protein, respectively) postulated to be important for nm23 function. DR-nm23 mRNA is preferentially expressed at early stages of myeloid differentiation of highly purified CD34+ cells. Its constitutive expression in the myeloid precursor 32Dc13 cell line, which is growth-factor dependent for both proliferation and differentiation, results in inhibition of granulocytic differentiation induced by granulocyte colony-stimulating factor and causes apoptotic cell death. These results are consistent with a role for DR-nm23 in normal hematopoiesis and raise the possibility that its overexpression contributes to differentiation arrest, a feature of blastic transformation in chronic myelogenous leukemia.